6m+4-3m=7(m-2)-2

Simple and best practice solution for 6m+4-3m=7(m-2)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6m+4-3m=7(m-2)-2 equation:


Simplifying
6m + 4 + -3m = 7(m + -2) + -2

Reorder the terms:
4 + 6m + -3m = 7(m + -2) + -2

Combine like terms: 6m + -3m = 3m
4 + 3m = 7(m + -2) + -2

Reorder the terms:
4 + 3m = 7(-2 + m) + -2
4 + 3m = (-2 * 7 + m * 7) + -2
4 + 3m = (-14 + 7m) + -2

Reorder the terms:
4 + 3m = -14 + -2 + 7m

Combine like terms: -14 + -2 = -16
4 + 3m = -16 + 7m

Solving
4 + 3m = -16 + 7m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-7m' to each side of the equation.
4 + 3m + -7m = -16 + 7m + -7m

Combine like terms: 3m + -7m = -4m
4 + -4m = -16 + 7m + -7m

Combine like terms: 7m + -7m = 0
4 + -4m = -16 + 0
4 + -4m = -16

Add '-4' to each side of the equation.
4 + -4 + -4m = -16 + -4

Combine like terms: 4 + -4 = 0
0 + -4m = -16 + -4
-4m = -16 + -4

Combine like terms: -16 + -4 = -20
-4m = -20

Divide each side by '-4'.
m = 5

Simplifying
m = 5

See similar equations:

| 3x-4(10)= | | x+9=y | | 2x^2-3x-464=0 | | -5-15-25= | | 20=-5(x-7) | | 128=4(7x+4) | | (1-3x)(x-1)= | | -8x-(x+6)=4-x | | 3(3x-1)+5x=5(5+x) | | -2y-3y+8=-5y-12 | | 9-9x=87-3x | | 5(2x+3)=4(3x+2)-3 | | 5x-2=4(x+1) | | 4(x-6)=6(x+2) | | 5(x+5)+9= | | 23x+-8+-14x=10 | | 2x+14=5x-8 | | n-4n-22=7n | | x(3+5)=7x-3 | | 2(x-4)+2x=32 | | 112-2x=5x-7 | | 2x-3-8x=-27 | | 1-3x(x-1)= | | 8x-7=9x+12 | | -147=-3+8a | | 4-6x=12x-7 | | 14(x^2)(y^2)+9xy-18=0 | | a/7+4=2 | | 5p-30=12 | | -1=5-4x-10-x+45 | | 4b+16=35 | | 3=-3k+9 |

Equations solver categories